Harnessing natural killer cells to develop next‐generation cellular immunotherapy. Issue 4 (2nd August 2022) - Liu, Siyao; Nguyen, Kaycee; Park, Dongyong; Wong, Nelson; Wang, Anson; Zhou, Yubin
Abstract: Cellular immunotherapy harnesses the body's own immune system to fight cancer by using engineered T cells, macrophages, or natural killer (NK) cells. Compared to chimeric antigen receptor T (CAR‐T) cells that are commonly used to treat hematological malignancies, CAR‐NK cells have shown remarkable therapeutic effectiveness while exhibiting enhanced safety, reduced risk of graft‐versus‐host disease, fewer side effects, and amplified antitumor efficacy. Preclinical trials have unveiled the high potential of adoptive CAR‐NK cell therapy to curtail or even eliminate both hematological malignancies and solid tumors in animal models. We brought forth herein the design principle of CAR‐NK cells, highlighted the latest progress in the preclinical testing and clinical trials of CAR‐NK cells, briefly delved into discussed major roadblocks in CAR‐NK therapy, and discussed potential solutions to surmount these challenges. Given the accelerated progress in both basic and translational studies on immune cell engineering, CAR‐NK cell therapy promises to become a serious contender and important addition to the next‐generation cell‐based immunotherapy. Key points: CAR‐NK cell therapy emerges as a promising immunotherapeutic option to curtail both hematological neoplasms and solid tumors by overcoming the resistant tumor microenvironment. CAR‐NK cell therapy exhibits a superior safety profile with effective cytotoxicity against tumor cells, making it a new addition to the fourth pillar of cancer therapy. Abstract : In this review, we highlight the latest progress in the CAR‐NK cell‐based immunotherapy. We also discuss major roadblocks facing the clinical translation of CAR‐NK cell therapy, and present potential strategies to surmount these challenges.